Zakat digital dalam perspektif hukum islam: peluang, tantangan, dan solusi praktis. - billah, ahmad nastain (Maliki Interdisciplinary Journal, 2026)
The development of digital technology has significantly impacted various aspects of life, including the practice of zakat. This article aims to examine the phenomenon of digital zakat from the perspective of Islamic law, focusing on identifying its opportunities, challenges, and practical solutions in the digital transformation era. This study employs a qualitative approach using library research methods, referring to primary sources such as the Qur'an, hadith, classical Islamic jurisprudence books, as well as contemporary legal documents and fatwas. The findings indicate that digital zakat offers considerable potential in terms of efficiency, accessibility, transparency, and increased public participation. However, it also faces critical challenges related to legal validity, contract legitimacy, digital literacy, and infrastructure. Therefore, strengthening regulation, contemporary ijtihad, and synergy between zakat institutions, the government, and sharia authorities are essential. Digital zakat has the potential to become a strategic solution in strengthening the Islamic economic system, provided it remains grounded in the principles of maqāṣid al-sharī‘ah.